1992
DOI: 10.1084/jem.175.5.1307
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro clonal deletion of double-positive thymocytes.

Abstract: StlmrllsryTo study the processes of thymic development, we have established transgenic mice expressing an or/3 T cell antigen receptor (TCK) specific for cytochrome c associated with class II major histocompatibility complex (MHC) molecules. The transgenic TCK chains are expressed by most of the thymocytes in these mice, and these cells have been shown to efficiently mature in association with E L and Ab-encoded class II MHC molecules. This report describes a characterization of the negative selection of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
74
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(80 citation statements)
references
References 47 publications
6
74
0
Order By: Relevance
“…1B and data not shown). Analysis of these mice show that transgenic T cells are positively selected in the H-2 b background, with skewing toward the CD4 ϩ CD8 Ϫ lineage as shown before (23). In the CD30 heterozygous, H-2 s background, negative selection takes place as evidenced by the absence of positive selection and severalfold drop of thymocyte cell number (Fig.…”
Section: Negative Selection In Tcr-transgenic Mice Does Not Appear Tomentioning
confidence: 95%
See 2 more Smart Citations
“…1B and data not shown). Analysis of these mice show that transgenic T cells are positively selected in the H-2 b background, with skewing toward the CD4 ϩ CD8 Ϫ lineage as shown before (23). In the CD30 heterozygous, H-2 s background, negative selection takes place as evidenced by the absence of positive selection and severalfold drop of thymocyte cell number (Fig.…”
Section: Negative Selection In Tcr-transgenic Mice Does Not Appear Tomentioning
confidence: 95%
“…The AND TCR is specific for pigeon cytochrome c and E k . In transgenic animals, transgene-expressing T cells are positively selected on A b molecule whereas negative selection occurs in the presence of A s (23). Negative selection can also be initiated by injection of pigeon cytochrome c peptide with mice in the H-2 k/b background.…”
Section: Negative Selection In Tcr-transgenic Mice Does Not Appear Tomentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that thymocytes that are specific for self peptides which are presented at low levels in the thymus (such as tissue-specific Ags) can, in some cases, evade negative selection and be exported to the periphery (8,9,22). Although these and other studies (23)(24)(25) suggest that negative selection can be sensitive to both the avidity of the autoreactive thymocyte for its cognate self peptide and the amount of self peptide that is presented in the thymus, how these parameters interact to determine the efficiency of negative selection of autoreactive CD4 ϩ T cells in vivo is not well understood.…”
mentioning
confidence: 96%
“…Further studies have demonstrated that even antigens that are unable to activate peripheral T cells expressing a defined T C R can induce TCR-specific thymocyte clonal deletion (50,51). In addition, experiments have shown that less antigen is required for clonal deletion than T cell activation (52,53). One interpretation of these studies has been that the requisite interactions for clonal deletion of thymocytes are less stringent than those required for T cell activation.…”
mentioning
confidence: 99%